First-Principles Study on the Electronic and Magnetic Properties of C- and N-Doped ZnS Nanowires (Journal of Atomic and Molecular Sciences, 2011)
We comparatively study the electronic and magnetic properties of unpassivated (NP) and H-passivated (HP) ZnS nanowire (NWs) doped with one C (or N) atom in terms of the first-principle calculation. The result shows that C (or N) atom preferring to the surface position for both of the NP and HP NWs. All of the C-doped ZnS NWs show semiconductor character. The magnetic moments are mainly contributed by the C-2p orbital. The magnetic moments of the C, Zn, and S atoms in the super cell have the same direction, indicating FM coupling between them. While for N-doped ZnS NWs, it is interesting that an N atom substituting an S atom in the middle position of NP ZnS NWs change the host from semiconductor to metal. These results show that the doping atom, doping position, and surface condition can significantly change the properties of semiconducting ZnS NWs.